Surgical anatomy of the aortic valve and root—implications for valve repair - De Paulis, Ruggero (Ann Cardiothorac Surg, 2019)
The aortic root is an important anatomical structure positioned at the center of the heart, making it critical to the functioning of the major cardiac chambers. Deep knowledge of the anatomical “surroundings” of the aortic root is crucial for surgeon attempting to spare or repair a leaking aortic valve. In fact, root dissection is a necessary step to “skeletonize” the aortic valve, allowing the surgeon to work on the critical components of its structure, namely the aorto-ventricular junction, the virtual basal ring (VBR) and the sino-tubular junction (STJ). These three components, along with the insertion of the leaflet to the aortic wall, form the skeleton of the aortic valve that is essential in guaranteeing valve competence. A good anatomical proportion between the various component of the skeleton of the aortic valve need to be verified, or re-established in order to set the basis for an optimal aortic valve repair. Once the skeleton of the heart has been correctly addressed, the condition of the valve leaflets need to be considered. Excess of leaflet tissue is treated by leaflet plication or resection and lack of leaflet tissue is addressed by tissue extension with autologous or heterologous materials. In the present manuscript, we highlight the principal structure of the aortic root and describe in detail each anatomical component. This basic anatomical knowledge is also important for a through understanding of the normal function of the valve and root structure during the cardiac cycle. The close boundaries existing between the left ventricular cavity and the aorta are important in explaining the sophisticated function of opening and closing of the aortic valve. Similarly, the role played by the sinuses of Valsalva in regulating the blood flow exiting the ventricle underline the concept that “form follows function” and emphasizes the importance of a good anatomical reconstruction for an optimal and long-lasting valve function.